Cooperation between HMGA1, PDX-1, and MafA is Essential for Glucose-Induced Insulin Transcription in Pancreatic Beta Cells - Arcidiacono, Biagio; Iiritano, Stefania; Chiefari, Eusebio; Brunetti, Francesco S.; Gu, Guoqiang; Foti, Daniela Patrizia; Brunetti, Antonio (Frontiers in Endocrinology, 2015)
The high-mobility group AT-hook 1 (HMGA1) protein is a nuclear architectural factor that can organize chromatin structures. It regulates gene expression by controlling the formation of stereospecific multiprotein complexes called “enhanceosomes” on the AT-rich regions of target gene promoters. Previously, we reported that defects in HMGA1 caused decreased insulin receptor expression and increased susceptibility to type 2 diabetes mellitus in humans and mice. Interestingly, mice with disrupted HMGA1 gene had significantly smaller islets and decreased insulin content in their pancreata, suggesting that HMGA1 may have a direct role in insulin transcription and secretion. Herein, we investigate the regulatory roles of HMGA1 in insulin transcription. We provide evidence that HMGA1 physically interacts with PDX-1 and MafA, two critical transcription factors for insulin gene expression and beta-cell function, both in vitro and in vivo. We then show that the overexpression of HMGA1 significantly improves the transactivating activity of PDX-1 and MafA on human and mouse insulin promoters, while HMGA1 knockdown considerably decreased this transactivating activity. Lastly, we demonstrate that high glucose stimulus significantly increases the binding of HMGA1 to the insulin (INS) gene promoter, suggesting that HMGA1 may act as a glucose-sensitive element controlling the transcription of the INS gene. Together, our findings provide evidence that HMGA1, by regulating PDX-1- and MafA-induced transactivation of the INS gene promoter, plays a critical role in pancreatic beta-cell function and insulin production.